Changing source waters on the Northeast US Continental Shelf: Variation in nutrient supply and phytoplankton biomass - Kevin D. Friedland; Paula Fratantoni; Adrienne Silver; Damian C. Brady; Avijit Gangopadhyay; Scott I. Large; Ryan E. Morse; David W. Townsend; Marjorie A.M. Friedrichs; D. Christopher Melrose (Continental Shelf Research, 2024)

Modelling the influence of mechanical-ecohydrological feedback on the nonlinear dynamics of peatlands - Adilan W. Mahdiyasa; David J. Large; Bagus P. Muljadi; Matteo Icardi (Ecological Modelling, 2023)

Coprosma autumnalis (kanono; Rubiaceae) in New Zealand: nomenclature, iconography and phenology - Mark F. Large; David J. Mabberley; Elise Wood (Kew Bulletin, 2020)

Net primary productivity and its control of the Middle Jurassic peatlands: An example from the southern Junggar coalfield - Yanan Li; Longyi Shao; Zhiming Yan; Haihai Hou; Yue Tang; David J. Large (Science China Earth Sciences, 2018)

Exploring drivers of litter decomposition in a greening Arctic: results from a transplant experiment across a treeline - Thomas C. Parker; Jonathan Sanderman; Robert D. Holden; Gesche Blume‐Werry; Sofie Sjögersten; David Large; Miguel Castro‐Díaz; Lorna E. Street; Jens‐Arne Subke; Philip A. Wookey (Ecology, 2018)
Decomposition of plant litter is a key control over carbon (C) storage in the soil. The biochemistry of the litter being produced, the environment in which the decomposition is taking place, and the community composition and metabolism of the decomposer organisms exert a combined influence over decomposition rates. As deciduous shrubs and trees are expanding into tundra ecosystems as a result of regional climate warming, this change in vegetation represents a change in litter input to tundra soils and a change in the environment in which litter decomposes. To test the importance of litter biochemistry and environment in determining litter mass loss, we reciprocally transplanted litter between heath ( Empetrum nigrum ), shrub ( Betula nana ), and forest ( Betula pubescens ) at a sub‐Arctic treeline in Sweden. As expansion of shrubs and trees promotes deeper snow, we also used a snow fence experiment in a tundra heath environment to understand the importance of snow depth, relative to other factors, in the decomposition of litter. Our results show that B. pubescens and B. nana leaf litter decomposed at faster rates than E. nigrum litter across all environments, while all litter species decomposed at faster rates in the forest and shrub environments than in the tundra heath. The effect of increased snow on decomposition was minimal, leading us to conclude that microbial activity over summer in the productive forest and shrub vegetation is driving increased mass loss compared to the heath. Using B. pubescens and E. nigrum litter, we demonstrate that degradation of carbohydrate‐C is a significant driver of mass loss in the forest. This pathway was less prominent in the heath, which is consistent with observations that tundra soils typically have high concentrations of “labile” C. This experiment suggests that further expansion of shrubs and trees may stimulate the loss of undecomposed carbohydrate C in the tundra.

Forest Management, Engineering, and Operations - Randy Kolka; Matt Powers; John Bradford; Brian Palik; Marty Jurgensen; Dalia Abbas; Tom Gallagher; Stephen Ambagis; Finto Antony; Lewis Jordan; Richard Daniels; Laurie Schimleck; et al. (Journal of Forestry, 2011)
9Forests represent a major global C sink, and forest management strategies that maximize carbon storage offer one avenue for mitigating increases in atmospheric carbon dioxide concentrations. Our understanding of relationships between forest management, productivity, carbon storage, and stand age, however, is limited. We established research plots in a chronosequence of thinned and unmanaged red pine stands in northern Minnesota to study patterns of carbon storage, and the major fluxes that influence carbon sequestration. We completed an inventory of all major C pools across a chronosequence of 57 red pine stands ages 9-306 years on the Chippewa National Forest in the fall of 2009. Results indicate total ecosystem C pools increase as red pine stands age for at least 150 years, and on-site C storage in thinned stands appears similar to unmanaged stands of comparable ages, despite different age-related trends in the live tree and forest floor pools. Thinned stands may have the potential to store more C than unmanaged stands in old age when C removed during harvesting is added into the total ecosystem C pool.

Contribution of subsurface peat to CO 2 and CH 4 fluxes in a neotropical peatland - EMMA L. WRIGHT; COLIN R. BLACK; ALEXANDER W. CHEESMAN; TREVOR DRAGE; DAVID LARGE; BENJAMIN L. TURNER; SOFIE SJÖGERSTEN (Global Change Biology, 2011)
Tropical peatlands play an important role in the global carbon cycling but little is known about factors regulating carbon dioxide (CO 2 ) and methane (CH 4 ) fluxes from these ecosystems. Here, we test the hypotheses that (i) CO 2 and CH 4 are produced mainly from surface peat and (ii) that the contribution of subsurface peat to net C emissions is governed by substrate availability. To achieve this, in situ and ex situ CO 2 and CH 4 fluxes were determined throughout the peat profiles under three vegetation types along a nutrient gradient in a tropical ombrotrophic peatland in Panama. The peat was also characterized with respect to its organic composition using 13 C solid state cross‐polarization magic‐angle spinning nuclear magnetic resonance spectroscopy. Deep peat contributed substantially to CO 2 effluxes both with respect to actual in situ and potential ex situ fluxes. CH 4 was produced throughout the peat profile with distinct subsurface peaks, but net emission was limited by oxidation in the surface layers. CO 2 and CH 4 production were strongly substrate‐limited and a large proportion of the variance in their production (30% and 63%, respectively) was related to the quantity of carbohydrates in the peat. Furthermore, CO 2 and CH 4 production differed between vegetation types, suggesting that the quality of plant‐derived carbon inputs is an important driver of trace gas production throughout the peat profile. We conclude that the production of both CO 2 and CH 4 from subsurface peat is a substantial component of the net efflux of these gases, but that gas production through the peat profile is regulated in part by the degree of decomposition of the peat.